Reform of the Juvenile Justice System Regarding the Age Limit for Criminal Responsibility - Yose Desman; Ahmad Redi (Syntax Idea)
This study examines the legal reform of the age limit for criminal responsibility of children within Indonesia's juvenile justice system, focusing on Law No. 11 of 2012, which sets a minimum age of 12 years. The research delves into the historical and legal evolution of juvenile justice in Indonesia, highlighting key legislative milestones and the impact of international conventions such as the Convention on the Rights of the Child. It also analyzes previous regulations affecting child protection and considers how legal reforms have aimed to balance accountability with the principle of the best interests of the child. Additionally, the study explores the adoption of the restorative justice approach as an alternative to punitive measures, emphasizing rehabilitation over retribution. Despite notable progress, the findings reveal persistent challenges in implementing these reforms, underscoring the need for stronger institutional frameworks and enhanced collaboration among relevant stakeholders to ensure comprehensive child protection.